Pengaruh Daya Tarik Wisata Kuliner Malaysia Terhadap Minat Berkunjung Wisatawan Indonesia - Suryadireja, Edgar Zefanya; Iqbal, Muhammad; Hariani, Dina (Institut Citra Internasional, 2025)
This study analyzes the influence of culinary attractiveness on the travel decisions of Indonesian tourists in the context of the growing trend of gastronomic experiences as a key motivation for modern international travel. The purpose of this research is to determine the extent to which culinary elements—including restaurant quality, the diversity of food locations, and the presence of food festivals—shape Indonesian tourists’ interest in choosing an overseas destination. A quantitative approach was employed using purposive sampling involving 100 respondents, with data collected through a Likert-scale questionnaire. The analysis utilized validity tests, reliability tests, normality tests, simple linear regression, t-tests, and the coefficient of determination. The findings indicate that all measurement indicators are valid and reliable, and that culinary factors exert a positive and significant influence on tourists’ behavioral tendencies, as evidenced by a significance value of 0.000 and a t-value of 19.367. The coefficient of determination (R² = 0.793) shows that 79.3% of the variation in tourists’ visit intention is explained by culinary attributes, while the remaining 20.7% is influenced by external factors. Overall, the study concludes that authentic and well-managed gastronomic experiences play a substantial role in enhancing Indonesian tourists’ motivation to travel and strengthening the competitiveness of international destinations.